Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1159/000025605
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1 Receptor Gene Polymorphism Is Associated with an Increased Vascular Reactivity in the Human Mammary Artery in vitro

Abstract: A gene polymorphism of the angiotensin II (AII) type 1 receptor has been described previously (A to C transversion at position 1166). Besides the epidemiological studies needed to determine a possible relationship between the polymorphism and some cardiovascular diseases, no study has been conducted to determine the impact of the polymorphism on vascular functions. At subthreshold concentrations, within the physiological range, AII potentiates α-adrenergic-dependent vascular tone. We investigated phenylephrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 16 publications
(39 reference statements)
3
26
2
2
Order By: Relevance
“…75 In vivo and in vitro studies of human arterial rings have shown that the constrictive effects of angiotensin II and phenylephrine are significantly amplified by comparison with the other genotype subgroups. 76 Finally, in hypertensive populations, subjects with AT 1 receptor gene polymorphism exhibit a greater pressure-independent decrease in aortic stiffness than the other genotypic subgroup for the same degree of convertingenzyme inhibition, whereas a comparable effect is not observed with calcium-entry blockade. 77 …”
Section: Stiffness Changes Associated With Sodium and Renin-angiotensmentioning
confidence: 98%
“…75 In vivo and in vitro studies of human arterial rings have shown that the constrictive effects of angiotensin II and phenylephrine are significantly amplified by comparison with the other genotype subgroups. 76 Finally, in hypertensive populations, subjects with AT 1 receptor gene polymorphism exhibit a greater pressure-independent decrease in aortic stiffness than the other genotypic subgroup for the same degree of convertingenzyme inhibition, whereas a comparable effect is not observed with calcium-entry blockade. 77 …”
Section: Stiffness Changes Associated With Sodium and Renin-angiotensmentioning
confidence: 98%
“…In this study, we have tested the hypothesis that genetic variations in the egfr gene shared between normal and malignant tumors could explain the observed clinical association. Several studies have revealed that polymorphic variations in genes encoding drug targets affect the response and toxicity to therapeutic agents (17)(18)(19)(20)(21)(22). The egff gene contains a highly polymorphic sequence in intron 1, which consists of a variable number of CA dinucleotide repeats ranging from 9 to 21 (23).…”
Section: Introductionmentioning
confidence: 99%
“…5 Some examples include polymorphisms in the b2-adrenoreceptors and sensitivity to b2-agonists in asthmatics, 6 polymorphisms in neurotransmitter-receptor-related genes and response to clozaphine in schizophrenic patients, 7 and polymorphisms in angiotensin II T1 receptor and vascular reactivity to phenylephrine. 8 The type 1 interferons, which include about 15 cytokines (13 isotypes of IFNa, one IFNb, one IFNo), all share the same receptor, IFNAR, for binding. 9 The two subunits of the receptor, IFNAR1 and IFNAR2, are coded by two different genes located close to each other on chromosome 21q22.1.…”
Section: Introductionmentioning
confidence: 99%